Infection patterns of Paradollfusnema amphisbaenia (Nematoda: Cosmocercidae) in a population of Amphisbaena wuchereri (Squamata: Amphisbaenidae) from Minas Gerais state, south-eastern Brazil, and its relations with host size, sex and fat body mass - Filogonio, R. [UNESP]; Toledo, G. M. [UNESP]; Anjos, L. A. [UNESP]; Rajão, B.; Galdino, C. A B; Nascimento, L. B. (Cambridge University Press (CUP), 2013)
Specimens (n= 41) of the amphisbaenid Amphisbaena wuchereri taken from a population in Minas Gerais state, south-eastern Brazil, were examined for gastrointestinal parasites. A single nematode species was found, Paradollfusnema amphisbaenia. This was a new host record for this nematode species. This parasite was encountered in the large intestine (prevalence of 100%), in the stomach (prevalence of 2%) and in the small intestine (prevalence of 7.3%). The intensity of infection ranged from 1 to 457 individual parasites per host and was positively correlated with body size of both male and female amphisbaenians. The discrepancy index (D) indicated that P. amphisbaenia tended to an even distribution in this host population. The nematode, which did not affect fat body mass, induced inflammatory infiltrations in the small intestine, indicating that the parasites might injure the host's organs. Copyright © Cambridge University Press 2012.
Keywords: Amphisbaena wuchereri; animal experiment; animal model; body mass; body size; Brazil; fat mass; female; large intestine; male; nematode; nematodiasis; nonhuman; Paradollfusnema amphisbaenia; sex; small intestine; squamate